Analysis Of Nurse Needs Using Workload Indicator Staff Need (WISN) Method - Sungkonoputri, Lisa; Dhamanti, Inge (Universitas Aisyah Pringsewu, 2023)
Human resource planning is the first step that must be taken by management to ensure the availability of the right workforce following their work. There needs to be a match between the needs of officers and the number of tasks they must perform so that health services can run well. This study aimed to determine the needs of nurses at the eye clinic of Adi Husada Undaan Wetan Hospital to improve the quality of its services. This quantitative descriptive research is conducted through interviews, direct observation, and reviewing hospital documents. The subject in this study was an optical refractionist who had additional duties as a nurse at an eye clinic. The calculation of nurse needs is carried out using the WISN (Workload Indicator Staff Need) method. The analysis results of the nurses' needs at the eye clinic of Adi Husada Undaan Wetan Hospital are two nurses and one optical refractionist. So, at the eye clinic of Adi Husada Undaan Wetan Hospital, there is a shortage of 2 nurses. The management of Adi Husada Undaan Wetan Hospital needs to consider adding nurses to the eye clinic.Keywords: workload; nurse; WISN; optical refractionist